Structural and Electrochemical Properties of Lanthanum Silicate Apatites La10Si6−x−0.2AlxZn0.2O27−δ for Solid Oxide Fuel Cells (SOFCs). (19th January 2021) - Afroze, Shammya; Absah, Hidayatul Qayyimah Hj Hairul; Reza, Md Sumon; Somalu, Mahendra Rao; Park, Jun-Young; Nekoonam, Saeed; Issakhov, Alibek; Azad, Abul Kalam
Abstract : An excellent oxide ion conductivity with high oxygen transportation of lanthanum silicate apatite at the solid oxide fuel cell (SOFC) can be achieved through the solid-state reaction method. The doped La10 Si6− x −0.2 Al x Zn0.2 O27− δ ( x  = 0.2 and 0.4) materials sintered at 1600°C accomplished crystallinity and crystal structure of apatite-type. The structural and electrochemical characterizations of La10 Si6− x −0.2 Al x Zn0.2 O27− δ ( x  = 0.2 and 0.4) were executed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and electrochemical impedance spectroscopy (EIS) measurements. The total oxide ion conductivities of La10 Si6− x −0.2 Al x Zn0.2 O27− δ ( x  = 0.2 and 0.4) were measured from low to intermediate operating temperature range (450 to 800°C) using electrochemical impedance spectroscopy. Room temperature XRD patterns of La10 Si6− x −0.2 Al x Zn0.2 O27− δ ( x  = 0.2 and 0.4) exhibited La10 Si6 O27 apatite phase with space group P 63 /m as the main phase with the minor appearance of La2 SiO5 as an impurity phase. The highest total oxide ion conductivity of 3.24 × 10 −3 Scm −1 and corresponding activation energy of 0.30 eV at 800°C were obtained for La10 Si5.6 Al0.2 Zn0.2 O26.7 which contains a low concentration of Al 3+ dopant.